(untitled) - Ginsberg, Leon H (Washington, DC, 1992)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Population -- Statistics; Social service -- United States -- Statistics; Population -- United States -- Statistics; Social Work -- United States -- Statistics; Dịch vụ xã hội -- Hoa Kỳ -- Thống kê; Công tác xã hội -- Hoa Kỳ -- Thống kê